Unraveling U. S. Health Care: A Personal Guide - Winter, Roberta E. (Rowman & Littlefield Publishers, 2013)
Unraveling U.S. Health Care is a guidebook to the health care system that provides a timely and thorough explanation of U.S. health care, written in readable laymen’s terms. Roberta Winter educates and informs general readers about useful information that will empower their health care decision making. She makes sense of important health care issues, which are often filtered with political and financial stakeholder bias, confusing the health care consumer. Useful tips, explanatory charts, and statewide scorecards are included throughout to assist readers in choosing the best care they can receive. More than ever, patients must act as consumers of health care, balancing informed decisions with available resources. Keeping this in mind, Winter also explores other options available to patients, including seeking health care outside the United States, and provides a roadmap for medical tourists to the U.S. In addition, she includes Medicare enrollment tips, and a summary of the 2010 health care reforms and implementation guidelines. Bringing all this data together, this book will serve as a resource and guide for anyone who seeks to receive better care for both everyday issues and major health concerns alike.